Educational level and colorectal cancer risk: the mediating roles of lifestyle and dietary factors. Issue 2 (March 2022) - Li, Lei; Fang, Yu-Jing; Abulimiti, Alinuer; Huang, Chu-Yi; Liu, Kai-Yan; Chen, Yu-Ming; Zhang, Cai-Xia
Abstract : Objective: The association between the educational level and colorectal cancer risk was controversial in developed countries and evidence was limited in Chinese population. This study aimed to investigate the association between the educational level and colorectal cancer risk in Guangdong Province, China. Methods: From July 2010 to April 2019, 2502 newly diagnosed colorectal cancer patients and 2538 sex- and age-matched controls were recruited in this case–control study. Multivariable logistic regression models were used to examine the association between the educational level and colorectal cancer risk. Path analysis was used to investigate whether behavioral risk factors potentially mediated the association between the educational level and colorectal cancer risk. Results: Educational level was inversely associated with the colorectal cancer risk. People who graduated from the college or above had a lower risk of colorectal cancer than those from the primary school or below, with an adjusted odds ratio of 0.42 [95% confidence intervals (CI), 0.34–0.52]. The total, direct and indirect effects of the educational level for the colorectal cancer risk were statistically significant in the path diagram. Path analysis showed that lower red and processed meat intake and higher tea and coffee drinking among high educational participants contributed to the inverse association between the educational level and colorectal cancer risk. Conclusion: The findings suggested that the educational level was inversely associated with the colorectal cancer risk. The association might be mediated by red and processed meat intake, household and leisure-time activities, and tea and coffee drinking.